Acute long-acting anticoagulant rodenticide poisoning in pregnancy: a case report - Jia, Yanxi; Zhan, Yongchi; Huang, Guiqiong; Deng, Chunyan; Yu, Haiyan (Frontiers in Pharmacology, 2024)
Introduction: Brodifacoum is a highly potent superwarfarin rodenticide that leads to coagulopathy.Although the effect of warfarin during pregnancy is well understood, reports on superwarfarin poisoning, like brodifacoum, during pregnancy are scarce.We report a case involving a woman with a singleton pregnancy who experienced sudden nasal hemorrhage accompanied by hematuria at 34 weeks and 3 days of gestation, with no apparent etiology. It was ultimately diagnosed as acquired coagulopathy resulting from brodifacoum poisoning. Fetal ultrasonography revealed significant intracranial hemorrhage, leading to intrauterine fetal demise and subsequent pregnancy termination. Following the correction of the patient's coagulation profile through intravenous and oral administration of vitamin K1, tailored to the serum levels of brodifacoum, diligent monitoring confirmed that the patient was in stable condition.The primary hazard associated with the ingestion of brodifacoum is hemorrhage, with clinical presentations varying from asymptomatic cases to overt bleeding, which may present as hematuria, epistaxis, menometrorrhagia, and intracranial hemorrhage. Therefore, the diagnosis and management of this type of poisoning pose significant challenges. Prompt recognition and ongoing care for pregnant individuals affected by rodenticide toxicity are crucial for optimizing maternal health outcomes.